(untitled) (L’architettura delle città - The Journal of the Scientific Society Ludovico Quaroni, 2013)
Measure originates in the intimate condition of an architect tried by the events of war, though firmly intent on returning to professional practice. Ludovico Quaroni returned to Italy in 1946 after spending more than five years in an Indian prison. His years of detention were undoubtedly a period of profound contemplation, but also a cultural experience that would develop new interests in all of his architectural and urban research. A lengthy period of suspension, about which Quaroni would say Â«I spent the entire War with nothing to doÂ», of self-criticism over the EUR, but also of the evolution of personal ideas about the culture of architectural space. It was an occasion for returning to the idea of the architecture of the city, what is more with an education in Oriental taste, a definitive comprehension of the great urban civilisation of the Middle East that, from a purely aesthetic attraction, was initially translated as a paradigm, as a term of comparison with European culture, and successively as an inspiration to the design of architecture, from the small to the large scale.